Unveiling the Full Dynamical and Reactivity Profiles of Acetylcholinesterase: A Comprehensive All-Atom Investigation - Célerse, Frédéric; Lagardère, Louis; Bouchibti, Yasmine; Nachon, Florian; Verdier, Laurent; Piquemal, Jean-Philip; Derat, Etienne (ACS catalysis, 2024)
Acetylcholinesterase is one of the most significant known serine hydrolases that governs the mammalian nervous system. Its high-rate speed, operating at the diffusion limit, combined with its buried active site feature, has made it a subject of extensive research over the last decades. Despite several studies focused on atomistic details of the different steps, a comprehensive theoretical investigation of the entire catalytic cycle has not yet been reported. In this work, we present an intuitive workflow aiming at describing the full dynamical and reactive profiles of AChE by coupling extensive steered molecular dynamics simulations for ligand diffusion and hybrid quantum mechanics/molecular mechanics computations to decipher the complete reactivity of the substrate within the enzyme. This comprehensive approach provides a broader view of the interconnections between each step that would not be readily accessible if the two steps were studied independently. Our simulations reveal that although individual steps do not indicate any strong limiting step, a solvent water molecule reorganization between the acylation and deacylation processes through the reactivity results in an energy cost of 20 kcal/mol. The observed barrier surpasses all others and discloses insights into a strong polarization effect acting on water molecules near the active site. An AMOEBA polarizable molecular dynamics simulation tends to confirm this assumption by capturing a substantial dipole moment (3.10 D) on the water molecule closest to the reaction site. These results shed light on the crucial correlation between this high-energy water reorganization and the polarization of confined water molecules. Consequently, carefully considering and modeling buried (polarizable) water molecules are of paramount importance when modeling full enzymatic activity. Therefore, this work will also provide valuable insights for future research on related enzymes with buried active sites.